Возраст и природа щелочных пород Дахунурского плутона, Юго-Восточная Тува - Врублевский В. В. Василий Васильевич; Никифоров А. В. Анатолий Викторович; Сугоракова А. М. Амина Мидхатовна; Лыхин Д. А. Дмитрий Алексеевич; Козулина Т. В. Тамара Викторовна; Юдин Д. С. Денис Сергеевич (Геохимия, 2014)
Заглавие с титульного листа